Oral Immunization with Recombinant Lactobacillus acidophilus Expressing espA-Tir-M Confers Protection against Enterohemorrhagic Escherichia coli O157:H7 Challenge in Mice - Lin, Ruqin; Zhang, Yiduo; Long, Beiguo; Li, Yawen; Wu, Yuhua; Duan, Siqin; Zhu, Bo; Wu, Xianbo; Fan, Hongying (Frontiers in Microbiology, 2017)
Enterohemorrhagic Escherichia coli O157:H7 (EHEC O157:H7) causes hemorrhagic colitis and the formation of characteristic attaching and effacing (A/E) lesions in humans. Given the severe sequelae of EHEC O157:H7 infection, and the lack of effective vaccines for human, it is critical to develop effective vaccines for human use. However, for achieving this goal many hurdles need to be addressed, such as the type or subset of antigens, adjuvant and the delivery route. We developed a candidate vaccine by inserting the bivalent antigen espA-Tir-M composed of espA and the Tir central domain into Lactobacillus acidophilus. The recombinant L. acidophilus (LA-ET) was safe in a cell model and excluded EHEC O157:H7 from LoVo cells at rates of nearly 94% and 60% in exclusion and competition assays, respectively. LA-ET inhibited the induction of A/E lesions by EHEC O157:H7 cells in vitro. Oral immunization with LA-ET induced higher levels of specific mucosal and systemic antibody responses in mice. Moreover, LA-ET enhanced interferon-γ and interleukin-4 and -10 production, which was associated with mixed helper T (Th1/Th2) cell responses, and protected against EHEC O157:H7 colonization and infection in mice at a rate of 80%. Histopathological analyses revealed that orally administered LA-ET reduced or inhibited A/E lesions and toxin-induced systemic injury. These findings demonstrate that LA-ET induces both humoral and cellular immune responses in mice and is therefore a promising vaccine against EHEC O157:H7 infection.